2006
DOI: 10.1093/rheumatology/kel223
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for gastrointestinal bleeding associated with non-steroidal anti-inflammatory drugs among elderly patients using low-dose aspirin: a retrospective cohort study

Abstract: Among elderly patients receiving cardiovascular protection with ASA and pain control with anti-inflammatory drugs, celecoxib may be safer with regards to GI toxicity than NS-NSAIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 57 publications
1
30
0
2
Order By: Relevance
“…In Quebec, aspirin is mainly prescribed on a continuous basis for the prevention of cardiovascular events as indicated by the daily dose prescribed (17). Indeed, after examining the data, we found that among patients classified as aspirin users, 96% filled prescriptions for aspirin in the followup with a mean Ϯ SD total duration of 645 Ϯ 402 days and a median total duration of 630 days (interquartile range 270 -1,014 days).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Quebec, aspirin is mainly prescribed on a continuous basis for the prevention of cardiovascular events as indicated by the daily dose prescribed (17). Indeed, after examining the data, we found that among patients classified as aspirin users, 96% filled prescriptions for aspirin in the followup with a mean Ϯ SD total duration of 645 Ϯ 402 days and a median total duration of 630 days (interquartile range 270 -1,014 days).…”
Section: Discussionmentioning
confidence: 95%
“…To further validate the diagnosis, we excluded hospitalizations where the GI diagnosis was considered a hospital complication. Previously, we had conducted an ad hoc analysis where we reviewed hospital charts of 30 patients from the Montreal General Hospital/McGill University Health Centre (17). These data indicated that 100% of the GI bleedings recorded as primary diagnoses were present on admission whereas 85% of all admissions for GI bleedings had GI bleeding recorded as the primary diagnosis on the hospital discharge summary.…”
Section: Data Sourcesmentioning
confidence: 99%
“…67 A study found that combining celecoxib and low-dose aspirin was associated with a lower risk than the use of ns-NSAIDs in combination with low-dose aspirin was. 63 Similarly, a meta-analysis showed that the relative risk of ulcer, bleeding, and perforation in patients using low-dose aspirin with COX-2-selective inhibitors and low-dose aspirin with ns-NSAIDs was 0.72 (95% confidence interval, 0.62-0.95). 60 However, conflicting data were reported in the MEDAL program, which compared etoricoxib with diclofenac in patients with osteoarthritis and rheumatoid arthritis taking low-dose aspirin, as it showed no significant difference between the 2 anti-inflammatory drugs.…”
Section: Gastrointestinal Risks Of Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…[63][64][65][66] The risk of upper GI events due to the use of ns-NSAIDs is aggravated by a simultaneous use of low-dose aspirin. 67 A study found that combining celecoxib and low-dose aspirin was associated with a lower risk than the use of ns-NSAIDs in combination with low-dose aspirin was.…”
Section: Gastrointestinal Risks Of Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…Von besonderer Bedeutung sind dabei Blutungen und thromboembolische Ereignisse. Neben Hirnblutungen stehen Blutungen bei akuten gastrointestinalen (GI) Ulzerationen und Perforationen im Vordergrund [12,13,14]. Sie resultieren aus dem Wirkungsmechanismus aller nicht-selektiven NSAR (tNSAR): ihrer Fähigkeit, die Aggregierbarkeit der Blutplättchen durch Blockade der Thromboxanproduktion zu vermindern und die strukturelle Organintegrität durch die Blockade der Bildung protektiver Prostaglandine (PGE 2 , PGI 2 ) zu erhalten [8,12].…”
unclassified